The implications of social media on local media business: case studies in Palembang, Manado and Bandung - Eni Maryani; Rahmawan, Detta; Siti Karlinah (Penerbit Universiti Kebangsaan Malaysia, 2020)
The implications of social media on the transformation of the media business are important issues in the study of the media industry. With the increasing penetration of the Internet in Indonesia and the proliferation of smartphone use, it is assumed that there are significant changes in media consumption patterns, especially for those who are often called millennials and generation Z. However, it is known that local media practitioners have yet to explore digital transformation properly, especially in terms of integrating social media platforms in various aspects of their business. This article used qualitative field research and observations to explore the perspectives of media practitioners in implementing social media in their business. Additional data were also collected from content analysis and exploration on all social media platforms owned by nine local media in Palembang, Manado, and Bandung. The result of the study revealed that the utilisation of social media is an innovation in the local media business, but it had not been optimally implemented. There is a disparity between the ideal expectations of social media use and the capabilities and knowledge of local media practitioners. In addition, the utilisation of social media in local media businesses has little impact on media income and the sustainability of the local media, since the context and ecosystem of the local media business are different from national media business located in Jakarta as the centre of economic activities in Indonesia.